Effect of acupressure at points ST18, SP6, and LI4 on breast milk production: A pre-post study in Solok Regency - Detty Afriyanti S.; Derry Trisna Wahyuni S.; Mevial Renanta (Journal of Health Technology Assessment in Midwifery, 2025)
Perceived insufficient breast milk is one of the most commonly reported challenges to achieving exclusive breastfeeding and is frequently influenced by psychological, emotional, and support-related factors rather than actual physiological milk insufficiency. Acupressure has increasingly been explored as a complementary, non-pharmacological approach to support maternal comfort and breastfeeding confidence. This study aimed to analyze the effect of acupressure on breast milk adequacy scores using validated lactation indicators among breastfeeding mothers in the working area of Tanjung Bingkung Public Health Center, Solok Regency, in 2024. A pre-experimental one-group pretest–posttest design was used, involving 30 respondents selected through purposive sampling. Breast milk adequacy was measured using a validated Breast Milk Adequacy Questionnaire combined with infant adequacy indicators, including feeding frequency, wet diaper count, and weekly weight gain. Scores ranged from low (0–1), moderate (2–3), to adequate production (≥4). Data were collected before and after a seven-day acupressure intervention and analyzed using a paired t-test. The mean breast milk adequacy score increased from 1.27 (SD 1.20) before the intervention to 2.50 (SD 0.73) afterward, representing an approximate 96.8% improvement from baseline. Statistical analysis showed a significant difference between pretest and posttest scores (p = 0.000). These findings suggest a potential supportive role of acupressure in improving perceived lactation adequacy among breastfeeding mothers. However, given the absence of a control group and the use of subjective measurement tools, further studies particularly randomized controlled trials are required to confirm causality and clarify the mechanisms involved.